Impact of the Whole Genome Duplication Event on PYK Activity and Effects of a PYK1 Mutation on Metabolism in S. cerevisiae - Chen, Hong; Blum, Jamie E.; Thalacker-Mercer, Anna; Gu, Zhenglong (Frontiers in Molecular Biosciences, 2021)
Background: Evolution of aerobic fermentation (crabtree effect) in yeast is associated with the whole genome duplication (WGD) event, suggesting that duplication of certain genes may have altered yeast metabolism. The pyruvate kinase (PYK) gene is associated with alterations in cell metabolism, and duplicated during the WGD, generating PYK1 and PYK2. Thus, the impact of WGD on PYK activity and role of PYK in yeast metabolism were explored. Methods: PYK activity in the presence or absence of fructose-1,6-bisphosphate (FBP) was compared between pre- and post-WGD yeast. Glucose consumption, ethanol production, and oxygen consumption were measured in wildtype yeast and yeast with a T403E point mutation, which alters FBP binding affinity. Results: FBP stimulated increased PYK activity in pre-WGD yeast and in the PYK1 isoforms of post-WGD yeast, but not in the PYK2 isoforms of post-WGD yeast. Compared to wildtype, T403E mutant yeast displayed reduced glucose consumption, reduced ethanol production, and increased mitochondrial metabolism. Conclusion: The WGD event impacted the sensitivity of PYK activity to FBP. Mutations in the FBP binding domain of PYK induce metabolic shifts that favor respiration and suppress fermentation.